Comparison of the Decision of the Medan District Court Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Mdn and Surabaya District Court Number 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby - Keliat, Venia Utami; Chandra Lahirisa Putra T Sibero; Ronald Sianipar (Universitas Ekasakti, 2024)
A brand is an identifying mark used specifically to distinguish one product from another.With the advancement of technology and information, many trademark disputes arise. Such as the litigation between MS GLOW and PS GLOW, these brands are also involved in trademark plagiarism lawsuits. So, how is the trademark dispute resolution between MS GLOW and PS GLOW carried out, and what legal protection efforts exist for the registered trademarks MS GLOW and PS GLOW concerning trade of goods in Indonesia. The method used in this research is a legal and regulatory approach, a case approach, and then a conceptual approach. The results of this research indicate that dispute resolution takes place in two commercial courts. The trial in the Medan Commercial Court ruled in favor of MS GLOW, whereas the trial in the Surabaya Commercial Court ruled in favor of PS GLOW. The verdict of the Surabaya Commercial Court concluded that the use of the MS GLOW brand did not align with the registered trademark group. The 'first to file' system is a preventive legal protection effort, while repressive legal efforts are carried out through the imposition of criminal sanctions.